Investigating Precipitation Changes in the Southern Coast of Iran using ERA5 Data - Maryam Kamali; Masoud Torabi Azad (Nīvār)
Precipitation is an important but variable quantity in the climate system. Monitoring the changes of this quantity has many complications, so in this research, we tried to investigate the trend of precipitation changes in the coastal strip of southern Iran using ERA5 data. In this regard, the monthly rainfall data of ERA5 model was used for the time period of 1981-2020. For this investigation, linear regression tests and Mann-Kendall test were used to measure the correlation and the trend of changes of this quantity in 3 provinces of Khuzestan, Bushehr and Hormozgan. Examining the results of the correlation between the observational data and the model data indicated a high and significant correlation, which showed a high correlation of 95 percent with a correlation coefficient of more than 0.92. Examining the time series of the data indicated an increase in regional rainfall in the spring season and a decrease in the winter season.Intra-seasonal changes showed that winter rains decreased compared to autumn rains, spring rains increased compared to autumn, summer rains increased compared to autumn rains, and summer rains increased compared to spring rains in the region. . The monthly survey of rainfall showed that the concentration of the increasing rate of rainfall was concentrated in the northern regions of Khuzestan province, which shows a significant upward trend in some regions such as the east of Hormozgan province in January.